For this case we must solve the following equation:
![\frac {2} {7} (x-2) = 4x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4r1hu05y82693w117ml59lxfp650xis27g.png)
So:
We apply distributive property to the terms within parentheses:
![\frac {2} {7} x- \frac {4} {7} = 4x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zpargs2srwwx0889vqvmse2x9xf61j7ibb.png)
Add
on both sides of the equation we have:
![\frac {2} {7} x = 4x + \frac {4} {7}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gfj339jcmqewk8l4qlc5suc8cr1cuk80hl.png)
Subtracting 4x from both sides of the equation we have:
![\frac {2} {7} x-4x = \frac {4} {7}\\\frac {2-28} {7} x = \frac {4} {7}\\\frac {-26} {7} x = \frac {4} {7}\\- \frac {26} {7} x = \frac {4} {7}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q7n2o8vcu0126jgv678l4vexuvo1l946vl.png)
We multiply by 7 on both sides of the equation:
![-26x = 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/16ekrh2gpiod75dicoy9v6nb2jkkjmeenv.png)
We divide by -26 on both sides of the equation:
![x = \frac {4} {- 26}\\x = - \frac {2} {13}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wdoe8obltzr978kl02kqwni3fbvol7fd3r.png)
ANswer:
![x = - \frac {2} {13}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bzn6on5ly9ewxqqdmpcsmug0y6e4wp26rr.png)